Creativity and cognitive reserve in old age: an exploratory study in the Portuguese population - Mendes,Andreia (2020)
The present study aims to investigate the relationship between creativity, particularly divergent thinking, and cognitive reserve (CR), in a sample of older adults without cognitive impairment. 53 community-dwelling subjects met the inclusion criteria and were submitted to the Creativity Test (ProCriativ) and the Cognitive Reserve Questionnaire (CRQ). The correlational analysis revealed that ProCriativ’s fluency and flexibility indexes were positively and significantly correlated with the CRQ. However, according to the backward stepwise regression analysis, only flexibility was a significant predictor of CRQ. Our results are in line with former studies that found a clear association between creativity and CR. Additionally, in other studies fluency and originality were also predictors of CR proxies besides flexibility. It is speculated that creativity could represent another indicator of CR. Further investigation is needed to corroborate the previous findings.